Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia dan Upah Minimum terhadap Tingkat Kemiskinan Melalui Tingkat Pengangguran di Kabupaten Tanjung Jabung Timurâ€ - Juniati Juniati; Junaidi Junaidi; Erni Achmad (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research aims to: 1) analyze the development of economic growth, human development index, minimum wage, unemployment rate and poverty rate in East Tanjung Jabung Regency; 2) analyze the influence of economic growth, human development index, and minimum wage on the unemployment rate in East Tanjung Jabung Regency; and 3) analyze the influence of economic growth, human development index, and minimum wage on poverty levels through unemployment rates in East Tanjung Jabung Regency. The path analysis method was used in this research. During the 2001-2021 period, the economic development of East Tanjung Jabung Regency experienced annual increases and decreases, with an average growth rate of 4.02 percent. During the 2001-2021 period, the human development index (HDI) of East Tanjung Jabung Regency fluctuated every year, but the average HDI over the entire period was 58.31. Then, the minimum wage in East Tanjung Jabung Regency continues to increase every year; However, minimum wage development there is still inconsistent, with an average growth rate of 13.25 percent. In addition, the development of the unemployment rate in East Tanjung Jabung Regency during the 2001-2021 period was marked by increases and decreases, with a level of 4.34 percent as the overall average. Likewise, the development of poverty levels in East Tanjung Jabung Regency during the 2001-2021 period experienced increases and decreases, with an average of 12.52 percent over the entire period. According to the results of the path analysis, the variable representing the Human Development Index has a significant influence on the unemployment rate in East Tanjung Jabung Regency. In contrast, the variables representing Economic Growth and Minimum Wage do not have a significant influence on the Unemployment Rate in this region. According to the path analysis results, the Human Development Index and Unemployment Rate variables both have a significant influence on the Poverty Level in East Tanjung Jabung Regency, but the Economic Growth and Minimum Wage variables do not have a significant influence on the Poverty Level.